Integrasi Bahasa Arab Dalam Hukum Islam : Sebuah Pendekatan Multidisiplin - Danil, Muhammad; Irmasani Daulay; Hamdanil; Syukri Iska (LPPM Universitas HKBP Nommensen, 2025)
The integration of Arabic in Islamic law is very important because Arabic is the original language of the Koran and Hadith, the two main sources of Islamic law. A deep understanding of Islamic law, or fiqh, requires a good knowledge of Arabic because the legal terms used in these texts often have nuances that can only be understood in the context of the original language. In Islamic law, the use of Arabic greatly influences the interpretation of religious texts. For example, small differences in word usage or grammatical structure can result in significant legal differences. Therefore, ulama and fuqaha (legal experts) often emphasize the importance of mastering Arabic to be able to understand, interpret and apply Islamic law correctly. Apart from that, Arabic is also used in worship rituals, such as prayers, prayer and reading the Koran, which is an integral part of the daily life of Muslims. Thus, the integration of Arabic in Islamic law is not only in the aspect of legal texts, but also includes daily religious practices.